Ramadan : the holy month of fasting - Khan, Ausma Zehanat (Orca origins., 2018)
Explores the origins, development, and traditions of the Islamic celebration of Ramadan through factual sidebars, color photographs, personal stories, recipes, and a glossary of terms.